Modal Sosial Kelompok Rentan Sebagai Upaya Disaster Risk Reduction (DRR) - Zeni Eka Putri; Azwar Azwar (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
Padang City has a low resilience for earthquake and tsunami disaster. Actually, social capital can be used as a strategy for overcoming impacts and efforts to reduce the level of risk of disaster. According to Siegler, social capital has four aspects, there are personal relationships, social network support, civic engagement, and trust and cooperative norms. The research objectives are: 1) Describe the knowledge and experience of vulnerable groups in dealing with disasters (earthquake and tsunami); 2) Identifying vulnerable groups' social capital as a disaster risk reduction (DRR) effort; 3) Describe the opportunities and obstacles/threats in the use of social capital as an effort to disaster risk reduction (DRR). The research method is qualitative with a case study. The location of this research in Pasie Nan Tigo, Koto Tangah District, Padang City. The determination of informants is a purposive sampling technique. This research has 22 informants. The criteria of informants are; 1) Have settled in a red zone area for at least 5 years; 2) The distance between the house and the beach is a maximum radius of 3 km. The results of the research are; 1) Vulnerable groups have the knowledge and experience about disasters; 2) Social groups already have social capital in 4 aspects of social capital such as personal relationships, social networking support, civic engagement, and trust and cooperative norm; 3) Social capital has opportunities and challenges from the internal and external side. Keywords: Social Capital, DRR